Masked hypertension in renal transplant recipients. (February 2014) - Kayrak, Mehmet; Gul, Enes Elvin; Kaya, Coskun; Solak, Yalcin; Turkmen, Kultigin; Yazici, Raziye; Guney, Ibrahim; Altintepe, Lutfullah; Turk, Suleyman; Ozdemir, Kurtulus
Abstract Purpose: Arterial hypertension is a risk factor affecting graft function in renal transplant recipients (RTRs). In pediatric RTRs, high prevalence of masked and nocturnal hypertension was reported. Most of the RTRs had a history of hypertension and some of them were normotensive at outpatient visits whereas home blood pressure (BP) levels were higher. Masked hypertension (MHT) is defined as a normal office BP but an elevated ambulatory BP. Previous reports have demonstrated the detrimental role of MHT in clinical outcomes in hypertensive patients. However, the true prevalence of MHT in RTRs is yet to be defined. Methods: A total of 113 RTRs (mean age 44 ± 16 years, 72 males, 41 females) with normal office BP (< 140/90 mmHg) were enrolled to the study from the outpatient renal transplantation clinic. Ambulatory BP monitoring (ABPM) was performed in all participants for a 24-h period. Average daytime BP values above 135 mmHg systolic and 85 mmHg diastolic were defined as MHT. Results: The prevalence of MHT in our cohort was 39% (n = 45). Fasting glucose and C-reactive protein levels were higher in patients with MHT compared with normal BP group (p = 0.02 and p = 0.04, respectively). RTRs with deceased donor type had higher prevalence of MHT than RTRs with living donor (40% vs 19%, p = 0.003). In multivariate analysis, deceased donor type could predict the MHT independent of age, gender, office systolic BP level, diabetes mellitus, serum creatinine, C-reactive protein, and glucose levels (OR = 3.62, 95% CI 1.16–11.31, p = 0.03). Conclusion: We demonstrated an increased prevalence of MHT in a typical renal transplant cohort. In addition, transplantation from a deceased donor may be a predictor of MHT. The prevalence of MHT may help to explain high rate of cardiovascular events in RTRs. Therefore, routine application of ABPM in RTRs may be plausible, particularly in RTRs with deceased donor type.